Penyuluhan Strategi Pengembangan Dalam Pemasaran Produk Usaha UMKM Pada Era Digital Di Desa A Widodo - Miki Indika; Suharto Suharto; Kusnadi Yudha Wiguna; Subianto Subianto; Herawati Herawati; Hanzila Hanzila (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service aims as literacy in the development strategy for marketing MSME products in A. Widodo Village, Tugumulyo District, Musi Rawas Regency. This activity was carried out with a lecture method with MSME actors and visual media supporting devices and ended with a question and answer session, very effective in delivering material. The enthusiasm of the participants in participating in this outreach activity became a measure of the success of the Community Service agenda. This is shown by the interaction between the presenters and the participants in the question-and-answer session